KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH (Studi Kasus Peran Kepala SMPN 8 Satap Liukang Tupabbiring Kabupaten Pangkajene dan Kepulauan) - Ramadhani, Sri Febrina; Wahira; Ardiansyah, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the transformational leadership of the Principal, this study aims to determine how the description of the role of transformational leadership of the Principal at SMPN 8 Satap Liukang Tupabbiring which includes dimensions of idealized influence, inspirational motivation, intellectual stimulation and support for subordinates (individualized consideration) and what are the supporting factors and inhibiting factors in carrying out the role of transformational leadership at SMPN 8 Satap Liukang Tupabbiring. The research method used is qualitative research with data collection techniques of interviews, observation and documentation. Data analysis techniques are carried out through four stages, namely data collection, data reduction, data presentation and drawing conclusions. The results of the study indicate that the transformational leadership of the principal includes dimensions (a) Idealized influence with indicators of having personal attraction (charisma), being a role model for subordinates and actions that can inspire teachers, (b) Inspirational motivation with indicators of creating a clear picture of a vision that can be optimistically achieved, involving teachers and staff in the preparation of the vision, mission, goals and work programs of the school and giving awards for subordinates' achievements, (c) Intellectual stimulation with indicators of stimulating subordinates to be creative and innovative, providing space for subordinates to actualize themselves and dividing institutional tasks professionally and proportionally, (d) Support for Subordinates (individualized consideration) with indicators of creating a supportive organizational environment and climate. paying attention to the needs of subordinates and delegating tasks to develop subordinates. Supporting factors for the principal's transformational leadership are the existence of adequate human resources and support from various parties. Inhibiting factors for the principal's transformational leadership are limited resources, geographical conditions